2015
DOI: 10.1002/adma.201404342
|View full text |Cite
|
Sign up to set email alerts
|

Materials Research at Shanghai Jiao Tong University

Abstract: Transformer architectures have exhibited remarkable performance in image super-resolution (SR). Since the quadratic computational complexity of the self-attention (SA) in Transformer, existing methods tend to adopt SA in a local region to reduce overheads. However, the local design restricts the global context exploitation, which is critical for accurate image reconstruction. In this work, we propose the Recursive Generalization Transformer (RGT) for image SR, which can capture global spatial information and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 226 publications
0
47
0
1
Order By: Relevance
“…It is reported that the recrystallization in Ni-based alloy (such as FM52 alloy) effectively reduces the DDC susceptibility. 18) In order to supplement the results of previous study, the phase transformation products and micro strain led by recrystallization in the CGHAZ of 2.25Cr-1.6W steel were analyzed in this study by x-ray diffraction (XRD), optical microscope (OM), scanning electron microscope (SEM), transmission electron microscope (TEM), electron backscatter diffraction (EBSD), and transmission-EBSD (T-EBSD). Moreover, the roles of recrystallization of these two types of cracking were compared.…”
Section: Microstructure and Micro Strain In The Cghaz Of 225cr-16w mentioning
confidence: 98%
See 2 more Smart Citations
“…It is reported that the recrystallization in Ni-based alloy (such as FM52 alloy) effectively reduces the DDC susceptibility. 18) In order to supplement the results of previous study, the phase transformation products and micro strain led by recrystallization in the CGHAZ of 2.25Cr-1.6W steel were analyzed in this study by x-ray diffraction (XRD), optical microscope (OM), scanning electron microscope (SEM), transmission electron microscope (TEM), electron backscatter diffraction (EBSD), and transmission-EBSD (T-EBSD). Moreover, the roles of recrystallization of these two types of cracking were compared.…”
Section: Microstructure and Micro Strain In The Cghaz Of 225cr-16w mentioning
confidence: 98%
“…ferent Materials Systems Though recrystallization had been reported to effectively reduce the high temperature cracking susceptibility in Ni-based alloy 18) and heat resistant steel, 7) the mechanisms might be different. In this section, these two different materials systems were compared.…”
Section: Analyzing the Role Of Recrystallization In Two Dif-mentioning
confidence: 99%
See 1 more Smart Citation
“…The kinematics models of the airship (21) are where ϕ, θ, and ψ are the pitch, the yaw, and roll angles, respectively. ½ x g y g z g is the position in ERF.…”
Section: Kinematics Model Of the Airshipmentioning
confidence: 99%
“…Consequently, the noise in pixels of IR image is also independent. Second, when researching the IR noise characters, Chen 24 obtains a conclusion that noise in short term and local window can approximately be viewed as temporal and spatial stationary Gaussian noise. These above two points illustrate that the noise in IR images is independent and identically distributed and they subject to Gaussian distribution.…”
Section: Target and Observation Modelsmentioning
confidence: 99%